Efek Penambahan Abu Serbuk Kayu Pada Lempung Plastisitas Tinggi Yang Distabilisasi Dengan Kapur Dan Semen - M Faizal Alridho; Soewignjo Agus Nugroho; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Deposits of high plasticity clays are lay in several locations in Pekanbaru such as Muara Fajar and Minas, Since higher clay plasticity found, soil strength will be reduced when its directly face offto water. Lime has a long time used as a material to reduce soil plasticity, as well as cement. Several types of ash (rice husk ash, fly ash etc.) have also been widely used to improve physical and mechanical properties of clay. Lot of sawing waste are located on the suburb of Pekanbaru city. Theexistence of waste will become a problem in the future. The wood ash was combined with lime and cement. This research was carried out by creating samples, with combining variation of lime and wood ash with clay's that contain 5% cement. Samples for CBR and UCS tests, were carried out withand without curing and soaking. Treatment of specimens was taken of 28 days for curing and 4 days for soaking of each test. The expansion of samples was observed to see swelling of each mixturevariation. This study aims to observe the addition of wood ash to behavior of plasticity, Unconfined Compressive Strength (UCS), Bearing Capacity and Swelling Potential of high plasticity clay. Research shows that for Muara Fajar clay's, by adding cement, lime, and wood ash gradually to the clay, value of plasticity index change from high plasticity clay to high plasticity silt. The maximum value of UCS and CBR occurs on mixture of 90% clay + 10% lime. The curing and soaking treatment also affect to the value of UCS and CBR test. The highest value of UCS and CBR was found in samples in curing of 28 days. The potential swelling pressure of each sample is only 3 kPa.Keywords: Cement, High Plasticity, Lime, Stabilization, Wood Ash